How Covid-19 Pandemic Reshaped Cultural Environment in Italy and Ukraine: Facebook Content Analysis - Kochkina, Nataliia; Riccardi, Marina (Jurnal The Messenger, 2021)
The need to incorporate cultural aspects into business practice is long-standing. The cultural environment in Ukraine and Italy was reshaped, especially during the Covid-19 pandemic. Social networks reflected such transformation both at the personal level and in the business activities of national companies on Facebook, Twitter, Instagram, and other media. Facebook pages were analyzed as the most popular social platform in Ukraine and Italy to reveal these changes. Content analysis of countries' leaders in retail, e-commerce, and service was carried out, namely EVA, Rozetka, and Nova Noshta for Ukraine; and Conad, Bottega Verde, and Italo Treno for Italy. Two-phase desk research was conducted with ten research questions for each cultural dimension encoded in a binary system. The research has shown that Ukrainian business still manifests collaborative problem solving, compliance with social standards, and the value of human life. It demonstrates a low level of power distance and uncertainty avoidance. Ukraine is gradually changing its paradigm of thinking to a more hedonic and individualistic similar to Western Europe. In contrast, Italy shows less respect for power in all its manifestations and a greater willingness to take risks than before. The country has become less goal-oriented, restrained, and masculine but more collectivistic.